2015
DOI: 10.1167/iovs.15-16882
|View full text |Cite
|
Sign up to set email alerts
|

Previous Driving Experience, but Not Vision, Is Associated With Motor Vehicle Collision Rate in Bioptic Drivers

Abstract: Previous nonbioptic driving experience, but not visual acuity or contrast sensitivity, was associated with yearly MVC rate in bioptic drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…It has been shown in a standardized road test that most already-licensed bioptic drivers (22 out of 23) were rated safe. 23 Recent studies also found that bioptic drivers' collisions rates were correlated neither with visual acuity 28 nor road test performance. 29 In a case report, an early bioptic adopter received his license in 1971 had 20/100 vision at that time, 30 and according to a report acquired from California Department of Motor Vehicles, his vision still remained 20/100 in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in a standardized road test that most already-licensed bioptic drivers (22 out of 23) were rated safe. 23 Recent studies also found that bioptic drivers' collisions rates were correlated neither with visual acuity 28 nor road test performance. 29 In a case report, an early bioptic adopter received his license in 1971 had 20/100 vision at that time, 30 and according to a report acquired from California Department of Motor Vehicles, his vision still remained 20/100 in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies of bioptic drivers, mostly without AMD, reported differences in training hours 23 and accident rates 26 between participants with prior nonbioptic driving experience (first licensed without a bioptic) and participants without any prior nonbioptic driving experience (first licensed with a bioptic). We therefore divided the younger, non-AMD bioptic drivers who responded to our survey into two groups: persons first licensed without a bioptic and persons first licensed with a bioptic.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent retrospective review of 237 licensed bioptic drivers who received their initial evaluation to determine visual eligibility for bioptic driving in a university-based clinic, only 4% had a diagnosis of AMD. 26 Yet, AMD is a major cause of central vision impairment in the United States. 27 , 28 With the advent of new antivascular endothelial growth factor treatments for neovascular AMD 29 , 30 there will be increasing numbers 31 , 32 of older people with AMD who retain visual acuity sufficient to meet the vision requirements for driving with a bioptic telescope (visual acuity without the telescope can be as low as 20/200 in some states).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study of the relationship between vision and bipotic drivers’ perfromance in road test 21 , showed that the hours of training, not any visual factors, were the predictive of road testing outcome. Also, Dougherty, Flom, Bullimore and Raasch 15 study on traffic collisions of a group of bioptic drivers found that more driving experience prior to the use of bioptic telescope correlated with lower possiblity of being involved in road crashes. Their study 15 did not find any significant relationships between vision (visual acuity and contrast sensitivity) and road collisions.…”
Section: Introductionmentioning
confidence: 98%
“…Also, Dougherty, Flom, Bullimore and Raasch 15 study on traffic collisions of a group of bioptic drivers found that more driving experience prior to the use of bioptic telescope correlated with lower possiblity of being involved in road crashes. Their study 15 did not find any significant relationships between vision (visual acuity and contrast sensitivity) and road collisions. Nonetheless, bioptic users who have driven safely for decades provide possibilities for targeted research on the relationship between vision and driving.…”
Section: Introductionmentioning
confidence: 98%